Temperature Control System for Water Heater with Servo Valve using PID Method: Sistem Pengendalian Suhu Pada Pemanas Air Dengan Servo Valve Menggunankan Metode PID - Pranda Prasetyo (Institut Riset dan Publikasi Indonesia, 2023)
In cold areas, hot water is an essential requirement. Generally warm or hot water is used for bathing, washing, or other household purposes. In general, there are various types of water heaters when viewed from the source of energy, some of which use solar, gas and electricity. In this study, a water heating system was created by adjusting the input water using a servo valve, so it is expected that the water heating will work faster and the resulting performance can be more stable. The smaller the servio angle, the faster the water heating occurs. The expected temperature is between 30 and 60 °C. This system uses the PID method to control the temperature. From the results of the PID control test on sample data, the set point value is 40?C with a Kp value = 0.02, a Ti value = 80 and a Td value = 20. The temperature that has been given by the PID control tries to maintain the set point temperature which has been set at 40 ?C . With values of Kp, Ti, and Td above the temperature can reach the setpoint within (±) 30 minutes.